Minimally invasive surgery of the liver - Casciola, Luciano; Calise, Fulvio (Updates in Surgery,, 2013)
The treatment of liver diseases comprises a significant component of the practice of any general surgeon, whether working in an academic, a general, or a community hospital. With the rapid expansion in knowledge and technology, the liver has also been approached laparoscopically in specialized centers, with well-recognized advantages for patients. This book aims to communicate the large body of experience that has now been accumulated in minimally invasive liver surgery, with comprehensive and up-to-date information on the newest techniques. After a concise description of the main tools and technology necessary to carry out safe laparoscopic and/or robot-assisted liver surgery, individual operative techniques are explained and illustrated. Each chapter includes introductory information, a summary of indications and contraindications, and a detailed description of surgical procedure, including potential complications of both the surgery and the postoperative care. Special efforts have been taken to ensure that the illustrations are accurate and informative. The text is supplemented by a DVD of different procedures as performed by leading European liver surgeons.